CO Multi-line Imaging of Nearby Galaxies (COMING). VII. Fourier decomposition of molecular gas velocity fields and bar pattern speed. (11th February 2019) - Salak, Dragan; Noma, Yuto; Sorai, Kazuo; Miyamoto, Yusuke; Kuno, Nario; Pettitt, Alex R; Kaneko, Hiroyuki; Tanaka, Takahiro; Yasuda, Atsushi; Kita, Shoichiro; Yajima, Yoshiyuki; Shibata, Shugo; et al.
Abstract: The 12 CO ( J = 1→0) velocity fields of a sample of 20 nearby spiral galaxies, selected from the CO Multi-line Imaging of Nearby Galaxies (COMING) legacy project of Nobeyama Radio Observatory, have been analyzed by Fourier decomposition to determine their basic kinematic properties, such as circular and noncircular velocities. On average, the investigated barred (SAB and SB) galaxies exhibit a ratio of noncircular to circular velocities of molecular gas larger by a factor of 1.5–2 than non-barred (SA) spiral galaxies at radii within the bar semimajor axis a b at 1 kpc resolution, with a maximum at a radius of R / a b ≈ 0.3. Residual velocity field images, created by subtracting model velocity fields from the data, reveal that this trend is caused by kpc-scale streaming motions of molecular gas in the bar region. Applying a new method based on radial velocity reversal, we estimated the corotation radius R CR and bar pattern speed Ωb in seven SAB and SB systems. The ratio of the corotation to bar radius is found to be in a range of $\mathcal {R}\equiv R_CR/a_b ≈ 0.8$ –1.6, suggesting that intermediate (SBb–SBc), luminous barred spiral galaxies host fast and slow rotator bars. Tentative negative correlations are found for Ωb vs. a b and Ωb vs. total stellar mass M *, indicating that bars in massive disks are larger and rotate slower, possibly a consequence of angular momentum transfer. The kinematic properties of SAB and SB galaxies, derived from Fourier decomposition, are compared with recent numerical simulations that incorporate various rotation curve models and galaxy interactions.